2010
DOI: 10.1111/j.1478-3231.2010.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and potential of hepatic microRNA-122 expression in hepatitis C

Abstract: Compared with in vitro findings, hepatic miR-122 expression is not correlated with HCV load in the human liver. Therefore, miR-122, by itself, is not a critical molecular target for HCV therapy. MiR-122 expression is inversely correlated with both functional and histopathological liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
84
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 38 publications
12
84
2
1
Order By: Relevance
“…Our data confirmed that serum miR-122 level positively correlated with hepatic miR-122 expression, hepatic HAI score, and serum ALT levels in patients with CHC, suggesting a positive correlation with hepatic necroinflammation as previously reported (22,23,25). Therefore, serum miR-122 level could reflect hepatic miR-122 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Our data confirmed that serum miR-122 level positively correlated with hepatic miR-122 expression, hepatic HAI score, and serum ALT levels in patients with CHC, suggesting a positive correlation with hepatic necroinflammation as previously reported (22,23,25). Therefore, serum miR-122 level could reflect hepatic miR-122 expression.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, miR-122 levels were shown to be negatively correlated with the expression of IRGs, indicating that CHC subjects with PNR have both lower pretreatment miR-122 levels and higher IRG levels. Another puzzling feature is that hepatic miR-122 expression in CHC patients was shown unrelated with the hepatic HCV load, and was inversely correlated with the severity of functional and histopathological liver damage (Morita et al, 2011). This paper therefore states that miR-122 by itself is not a critical molecular target for HCV therapy.…”
Section: Mir-122 In Hcv Infectionmentioning
confidence: 92%
“…(10) The expression levels of microRNA-18a (miR-18a) and microRNA-199a-5p (miR-199a-5p) were quantified by the relative standard curve method using a control sample (histopathologically NL sample from a patient with a metastatic liver tumor) and normalized according to the level of expression of RNU6B.…”
Section: Quantitative Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…(7)(8)(9) MiRNAs are implicated in many biological processes and diverse diseases, such as viral infections and cancers. (10)(11)(12)(13) Recently, metastasis-related miRNAs in HCC were analyzed by comparing primary hepatocellular carcinoma (T) and noncancerous liver (N) (14) or T, adjacent venous tumor thrombus, and N. (15) In HCC, cancer metastasis is very complex with multiple steps, including local invasion, intravasation, survival in the circulation, extravasation, and colonization, which is accompanied by the accumulation of genetic and epigenetic alterations. (16) Furthermore, metastatic clones are derived from only a few clones in the genetically heterogeneous primary cancer.…”
mentioning
confidence: 99%